2021
DOI: 10.1038/s41598-021-85148-y
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of dendritic cell and monocyte subsets are associated with disease severity and mortality in liver cirrhosis patients

Abstract: Liver cirrhosis is often complicated by an immunological imbalance known as cirrhosis-associated immune dysfunction. This study aimed to investigate disturbances in circulating monocytes and dendritic cells in patients with acute decompensation (AD) of cirrhosis. The sample included 39 adult cirrhotic patients hospitalized for AD, 29 patients with stable cirrhosis (SC), and 30 healthy controls (CTR). Flow cytometry was used to analyze monocyte and dendritic cell subsets in whole blood and quantify cytokines in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 47 publications
0
16
0
7
Order By: Relevance
“…In cirrhotic patients, [130], Cardoso et al observed an increase in circulating intermediate monocytes (CD14 + CD16 + ), distinguished from the classical monocytes (CD14 ++ CD16 − ) and from nonclassical monocytes (CD14 −/low CD16 + ) [131]. They detected alterations in the proportions of circulating monocytes, particularly in patients with more advanced liver disease.…”
Section: Bone-marrow/monocyte-derived Macrophagesmentioning
confidence: 98%
“…In cirrhotic patients, [130], Cardoso et al observed an increase in circulating intermediate monocytes (CD14 + CD16 + ), distinguished from the classical monocytes (CD14 ++ CD16 − ) and from nonclassical monocytes (CD14 −/low CD16 + ) [131]. They detected alterations in the proportions of circulating monocytes, particularly in patients with more advanced liver disease.…”
Section: Bone-marrow/monocyte-derived Macrophagesmentioning
confidence: 98%
“…This is consistent with emerging data demonstrating that imbalance of Th cells promotes NAFLD and chronic liver diseases (He et al, 2017;Zhang et al, 2021). A very recent report demonstrated that patterns of dendritic cells and monocyte subsets are associated with the severity and mortality of patients with liver cirrhosis (Cardoso et al, 2021). In fact, an equilibrium Th1 = Th17 = Th2, NKT = NK, M1 = M2 pattern; semi-equilibrium Th1 = Th17 > Th2, CD8 + = CD4 + , NKT = NK pattern; or predominant CD8 + > CD4 + , Th1 > Th17 > Th2, NKT > NK, M1 > M2 pattern could each exhibit distinctively collective functions independent from the cellular components.…”
Section: Discussionmentioning
confidence: 99%
“…For flow cytometry immunophenotyping, the monoclonal antibodies CD62L (FITC, LT‐TD180), CD4 (PerCP, MEM‐241), and CD11c (PerCP Cy5‐5, BU15) from Exbio; CD10 (PECy7, HI10A), CD3 (APCH7, SK7), CD16 (FITC, 3G8), CD19 (APCH7, HIB19), CD20 (APCH7, 2H7), CD45 (PacO, HI30) and HLA‐DR (PacB, L243) from BD Biosciences; and CD56 (PE, N901 NKH‐1), CD14 (APC, RMO52), and CD123 (PE, SSDCLY107D2) from Beckman Coulter were used. Staining was based on an eight‐colour panel, as previously described by Cardoso and Santos‐Silva (2019) for the identification of monocytes, neutrophils and DCs [ 22 , 23 ]. The expression of CD56 on monocytes and CD62L on monocytes and neutrophils was determined using different panels, which also had markers for these cell lines (HLA‐DR, CD4 and CD45) [ 23 ].…”
Section: Methodsmentioning
confidence: 99%